Koi Fish Pond Monitoring System Using IoT - Sukarno, Setyawan Ajie; Maulana, Gun Gun; Andrea, Ferdyan (Universitas Muhammadiyah Surakarta, 2024)
The process of collecting water parameter data for koi fish ponds is still done manually. Each parameter from the manually collected samples is tested one by one. This process is inefficient and can cause delays in decisionmaking for koi fish farmers. If the manual testing reveals results that exceed the ideal threshold, it can have a negative impact on the fish. To address this issue, a koi fish pond water parameter monitoring system was designed using an automated method based on the Internet of Things. The sensors used in this study include an ultrasonic sensor, turbidity sensor, Total Dissolved Solids (TDS) sensor, and pH sensor. Based on the test results, when the values of the turbidity and TDS sensors exceed the set parameter limits of 40 NTU and 400 PPM, respectively, the system will activate the draining pump until the water level reaches the lower limit (10 cm), after which the filling pump will activate until the upper water level limit (18 cm) is reached. If the pH sensor value is below the lower limit set in the parameter, the system will activate the alkaline liquid pump to neutralize the pH to a value of 7. Conversely, if the pH sensor value exceeds the upper limit set in the parameter, the system will activate the acidic liquid pump to neutralize the pH back to 7. This automatic draining and filling system will stop working when the turbidity, TDS, and water level values fall within the parameters set in Blynk. The system also maintains the pond's water level at the upper limit set in the parameters.